Current agrobiodiversity status in two villages Tenh Phong and Quai To, Tuan Giao commune, Dien Bien province for sustainable socio-economic development - Anh Tuan, Tran; Haan Stefan, De; Ngoc Kiem, Truong (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 2S, 2017)
Agrobiodiverstiy plays a crucial role since it affects directly on the sustainability of agricultural system. However, studies on agrobiodiversity in Vietnam is still really limited. This study uses information about crops, livestocks in order to assess agrobiodiversity in Tenh Phong and Quai To villages, Tuan Giao district, Dien Bien province. Results show that agricultural ecosystem in the study area has quite abundant biodiversity with 121 plant species, including many scientifically valuable staple-food crops, and a variety of livestocks. In addition, because of the differences in environmental and socio-economic conditions, the distribution and frequency of species/varieties in two villages are not similar. Nevertheless, the similarity between Tenh Phong and Quai To villages is low efficiency of production due to the usage of traditional agricultural techniques, particularly in Tenh Phong village. This study can be used for planning of agricultural development, improving local people’s livelihoods, as well as biodiversity conservation, sustainability of agricultural ecosystem in Dien Bien province.